Sky Blue Water : Great Stories for Young Readers - Morgan, Collette A.; Peterson, Jay D. (Book collections on Project MUSE., 2016)
A collection of short stories featuring the diverse people and places of Minnesota, set in time periods from Prohibition to the present day.